Magnitude and Predictors of Dietary Diversity among HIV-Infected Adults on Antiretroviral Therapy: The Case of North-Western, Ghana - Louis Nebayeng Mornah; Mahama Saaka; Diana Pireh (AIDS Research and Treatment, 2024)
Introduction. Though people living with HIV/AIDS require a good combination of antiretroviral therapy and healthy dietary habits for a quality life and positive medical outcomes, little is, however, known regarding the dietary practices of HIV-positive patients who receive antiretroviral therapy (ART) in the Lawra Municipality. Objective. This study assessed the magnitude and factors associated with dietary diversity among HIV-positive patients on antiretroviral therapy (ART). Methods. This study was a facility-based cross-sectional study of 269 study participants recruited using a systematic random sampling technique. Bivariate and multivariable logistic regression analyses were performed to identify factors associated with their dietary diversity. Results. This study shows that only 36 (13.4%) of the sample consumed a diversified diet with a mean dietary diversity score of 3.7 ± 0.99. Starchy staple foods (96.7%) and flesh food (92.9%) were the most consumed foods. Being a nonfarmer employee (AOR = 10.76, 95% CI = 1.03–112.35), not taking cotrimoxazole prophylaxis (AOR = 3.76, 95% CI = 1.02–14.37) and adults of age 18–27 years (AOR = 5.95, 95% CI = 1.18–30.07) were significant predictors of high dietary diversity. Conclusion. This study revealed that dietary diversity was a significant nutritional problem among HIV-positive adults in Lawra Municipal Hospital. Starchy staple foods and flesh food were the most consumed foods, while organ meats, dairy products, and eggs were eaten less. Having a secured salary paid job, not taking cotrimoxazole prophylaxis, and being a young adult were strong predictors of a high dietary diversity score. Therefore, efforts should be made to strengthen and improve the economic status and to educate these vulnerable groups on the need to adhere to cotrimoxazole prophylaxis uptake.